Application of Science and Technology in Intellectual Property Rights Process Patent - Tanggahma, Biloka (Journal of Law, Politic and Humanities, 2023)
This research aims to analyze, explain and understand the application of science and technology to intellectual property rights in process patents and to analyze, explain and understand legal protection for process patents. The type of research used is empirical legal research because it is motivated by the idea that law cannot be separated from people's lives in the form of values and attitudes/behavior, but law can be studied from its empirical aspect, namely how the law is in reality in people's lives. The results of this research reveal that the application of IPTEKS and Intellectual Property Rights in the patent process means that Indonesian society as a society does not respect Intellectual Property Rights. The reality in society still shows that there are many violations of Patent Rights and it is suspected that they have reached a dangerous level and can damage the order of life in society in general, especially creativity to give birth to new discoveries. Meanwhile, legal protection for process patents developed by indigenous Papuans according to the Patent Law is granted on the basis of an application. And until December 2021, through the Trade and Small and Medium Industry IPR Consultation Clinic, the Papua Province Industry and Trade Service, several inventions regarding traditional medicines have been registered at the Patent Office in Jakarta. The form of legal protection can be seen from the application of Law Number 13 of 2016 concerning Patents